Peculiarities of hydrogen negative ion beams extraction from axially symmetric source with crossed fields - Goretskii, V.P.; Dobrovolskiy, A.M. (Вопросы атомной науки и техники, 2015)
A comparison of emission features of axially symmetric H⁻ ion source with magnetron discharge and H⁻ source which incorporates additional hollow cathode discharge in series with main one is presented. It is shown that in the last case concentration of H⁻ ions in a region of emission hole of the source essentially increases. H⁻ ion current from the source with additional discharge increases by an order of magnitude. Additional plasma drift from assisting discharge and cooling of electrons at their passing through magnetic field region are considered as the reasons of determined growth of concentration of negative ions. H⁻ current density value of 150 mA/cm2 on emission aperture of ion source is reached.